Differences in Speed of Response of Depressive Symptom Dimensions in Older Persons During Electroconvulsive Therapy. Issue 1 (March 2019) - Veltman, Eveline M.; van Hulten, Sophie; Twisk, Jos; Dols, Annemiek; van Exel, Eric; Stek, Max L.; Sienaert, Pascal; Bouckaert, Filip; van der Mast, Roos C.; Rhebergen, Didi
Abstract : Introduction: Electroconvulsive therapy (ECT) is an important and effective treatment for depression. However, research on course trajectories of depressive symptoms during ECT is limited. Insight into putative differences in speed of response of depressive symptom dimensions may enable clinicians to optimally inform patients and their relatives. Therefore, we aim to examine course trajectories of depressive symptom dimensions in depressed older persons during ECT. Methods: Data were derived from the Mood Disorders in Elderly treated with Electro Convulsive Therapy study, including 110 persons, aged 55 years or more, with a current diagnosis of major depressive disorder and referred for ECT. Exploratory factor analysis was used to identify symptom dimensions, using the 10 depression items of the Montgomery-Åsberg Depression Rating Scale (MADRS). Differences in course trajectories of symptom dimension during 2 weeks were examined by multilevel analyses. Results: Three symptom dimensions were identified: a "mood, " "melancholic, " and "suicidal" dimension. Mood showed a significantly greater severity decline as compared with melancholic and suicidal at the 1-week follow-up. At the 2-week follow-up, both mood and melancholic demonstrated a significantly greater decline as compared with suicidal. However, because scores on the suicidality item of the Montgomery-Asberg Depression Rating Scale were already lower at baseline compared with the other items, a floor effect cannot be ruled out. Discussion: All symptom dimensions of depression showed a rapid response to ECT. Our findings did not support the general assumption that suicidal symptoms may be the first to improve. However, a floor effect on the suicidality item cannot be ruled out. Abstract : Supplemental digital content is available in the text.